Community Health Center Efficiency. The Impact of Organization Design and Local Context: The Case of Indonesia - Suwatin Miharti; Rafael Wittek; Bart Los; Liesbet Heyse (Kerman University of Medical Sciences, 2022)
Background  The decentralization of the Indonesian healthcare system, launched in the year 2000, allowed the authorities of local community health centers (CHCs) to tailor their services to the needs of their clients. Many observers see this as an opportunity to increase CHC efficiency. Building on the Context Design Performance Framework, this paper assesses the extent to which efficiency variations between CHCs can be explained by the degree of fit between their organizational design characteristics and aspects of the communities in which they are embedded.   Methods  Data envelopment analysis (DEA) was applied to construct a measure of CHC efficiency for a sample of 598 CHCs in 2011, drawn from a publicly available Ministry of Health (MoH) dataset. Tobit regression analysis was applied to assess the impact of organization design and community characteristics and their interplay on efficiency. Results Large variations in CHC efficiency were discovered, suggesting that not all CHCs are equally capable of finding the optimal design to operate most efficiently. A significant inverted U-shape relationship was found for the organization design-efficiency link: efficiency is highest for CHCs with 1-2 horizontal units and decreases for CHCs exceeding or not reaching this number. No significant association was found between community characteristics (proportion of poor people, remote location of CHC) and CHC efficiency.  Conclusion  Organizational design matters for CHC efficiency, but no evidence was found for the hypothesis that a better fit between community characteristics and CHC design increases efficiency. A potential reason for this might be that CHC management's main design challenge is how to cope with the scarce availability of well-trained health personnel.